2016
DOI: 10.1038/srep28797
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary resistant starch type 4 on human gut microbiota and immunometabolic functions

Abstract: Dietary modulation of the gut microbiota impacts human health. Here we investigated the hitherto unknown effects of resistant starch type 4 (RS4) enriched diet on gut microbiota composition and short-chain fatty acid (SCFA) concentrations in parallel with host immunometabolic functions in twenty individuals with signs of metabolic syndrome (MetS). Cholesterols, fasting glucose, glycosylated haemoglobin, and proinflammatory markers in the blood as well as waist circumference and % body fat were lower post inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
141
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 47 publications
16
141
0
3
Order By: Relevance
“…A previous clinical trial reported that T2D and hyperlipidaemia patients were ameliorated by metformin and a herbal formula with increased abundance of Bautia , which was correlated significantly with the improvement in circulating glucose and lipids 52. Also, in line with a clinical trial in which Blautia was found to be negatively associated with TC and non-HDL-C, we observed similar negative associations between Blautia and blood lipid profiles 53. The enrichment of Blautia in the lower-fat group suggested that the diet-induced change in gut microbiota might be related to the host lipid homoeostasis in healthy young adults and possibly, be a future target for the management of subjects with cardiometabolic diseases.…”
Section: Discussionsupporting
confidence: 88%
“…A previous clinical trial reported that T2D and hyperlipidaemia patients were ameliorated by metformin and a herbal formula with increased abundance of Bautia , which was correlated significantly with the improvement in circulating glucose and lipids 52. Also, in line with a clinical trial in which Blautia was found to be negatively associated with TC and non-HDL-C, we observed similar negative associations between Blautia and blood lipid profiles 53. The enrichment of Blautia in the lower-fat group suggested that the diet-induced change in gut microbiota might be related to the host lipid homoeostasis in healthy young adults and possibly, be a future target for the management of subjects with cardiometabolic diseases.…”
Section: Discussionsupporting
confidence: 88%
“…Isovalerate is a degradation product of the branched-chain amino acid valine and is modulated by both mammalian and bacteria metabolism (11). Alterations in the gut microbiota owing to changes in salt intake might alter carbohydrate fermentation and contribute to increased production of short-chain fatty acids such as isovalerate (34). Urate (a purine derivative) increased with sodium restriction, as observed previously (35).…”
Section: Discussionmentioning
confidence: 55%
“…in the gut, while type 2 resistant starch increases Ruminococcus bromii and Eubacterium rectale spp. in humans and Bifidobacterium , Akkermansia and Allobaculum genera in mice [4,52,53]. Type 3 resistant starch is considered the most resistant form of resistant starch [54].…”
Section: Important Dietary Components For the Gut Microbiotamentioning
confidence: 99%